Peripheral Blood Lymphocyte Subsets as Biomarkers for the Severity of Inflammatory Bowel Disease Subtypes: A Cross-Sectional Study - Anwar Hassan Aljaf, Karwan; Ahmed Hama, Salih; Mohammed Raheem, Mohammed Omer (Journal of Contemporary Medical Sciences, 2024)
Objectives: This study aimed to assess IBD severity and its prognostic activity using peripheral blood lymphocyte subsets. Methods: The study was conducted on 46 patients with Crohn’s disease (CD), 55 with ulcerative colitis (UC), and 20 healthy controls (HCs). Based on the Harvey-Bradshaw Index (HBI) and Mayo score, patients were classified into remission or active status. Blood samples were collected from patients and analyzed for CD3+, CD4+, CD8+, CD4+/CD8+ ratio, and CD19+ proportions. Differential leukocytes, platelets, albumin, globulin, C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and faecal calprotectin were also assessed. Results: CD4+, CD8+, and CD19+ proportions were increased in CD and UC patients, while CD3+ was declined. CD4+ and CD19+ were elevated in remission and active CD, but CD8+ was changed only in active CD. Among UC patients, lymphocyte subsets were elevated in remission and active status. CD19+ positively correlated with CD severity. Consequently, CD19+ combined with inflammatory markers was highly significant in CD. Conclusion: These results suggest that peripheral blood lymphocyte subsets are good biomarkers for the IBD severity and prognostic activity with great clinical application values.